ANALISIS BENTUKAN LAHAN DI SEPANJANG BUKIT BARISAN, KABUPATEN PESISIR BARAT, PROVINSI LAMPUNG - Muzani Jalaludin; Henry Giovano; Mush'ab Baihaqy Giovano (Geography Education Study Program, Universitas Samudra, 2021)
This article discusses the characteristics of landforms in Pesisir Barat Regency. Pesisir Barat Regency is one of the regencies located in the western part of Lampung Province, having an area of ± 2,907.23 Km2 and having a coastline of 221.5 Km (land and islands). The study was conducted by overlaying the slope and altitude maps from the SRTM (Shuttle Radar Topographic Mission) by presenting a map. Variables used to determine the shape of coastal land are material and relief. These results indicate that the West Coastal Regency consists of structural landforms that occur due to the activity of the Semangko fault and the activity of underwater movement with the tectonic plate junction.